The effect of good corporate governance mechanism and corporate social responsibility on financial performance with earnings management as mediating variable - Mayang Mahrani; Noorlailie Soewarno (Asian Journal of Accounting Research, 2018)
The purpose of this paper is to determine the direct influence of the mechanism of good corporate governance (GCG) and corporate social responsibility (CSR) on financial performance as well as through earnings management as a mediating variable.The data used in this research are secondary data involving 102 companies listed on the Indonesian Stock Exchange for the period 2014. The data used in this study were analyzed using partial least square and carried out with the help of software WarpPLS 5.0.The results show that the mechanism of GCG and CSR has a positive effect on financial performance as well as the CSR on financial performance.The results also show partial mediation of earnings management on impact of GCG mechanisms on financial performance and full mediation of earnings management on impact of CSR on financial performance.